ACCOUNTING INFORMATION: CONCEPTUAL APPROACHES AND THE IMPACT ON ECONOMIC DECISIONS - Liliana LAZARI; Irina IAVORSCHI; Maia BAJAN (Economica)
This article examines the key concepts related to accounting information, as well as their impact on economic decisions. The research aims to clarify the essence of the concepts related to accounting information and the correct approach to these concepts, as well as to examine their structure according to various criteria. The pro- posed study investigates the impact of conceptual frameworks on the strategic management decisions within entities, as well as evaluates the extent to which conceptual changes affect the transparency and usefulness of accounting information for external users. Accounting information provides the foundation for assessing financial position and performance, managing risks, and supporting strategic planning. It is essential for making infor- med decisions and ensuring transparency and confidence in the economic environment. The study outlines the relevant concepts, structure, and applicability of accounting information in the decision-making process.